1988
DOI: 10.1038/334494a0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-induced binding and transcriptional efficacy of nuclear factor CREB

Abstract: A nuclear protein, CREB, has been isolated from rat brain and shown to stimulate transcription of the cyclic AMP-responsive gene somatostatin as a dimer. Biochemical analysis suggests that dimerization and transcriptional efficacy of CREB protein in vitro are regulated by phosphorylation. These findings demonstrate that cellular signals can modulate gene expression by regulating the covalent modification of pre-existing nuclear factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
659
3
8

Year Published

1989
1989
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,292 publications
(698 citation statements)
references
References 16 publications
28
659
3
8
Order By: Relevance
“…[16][17][18][19][20][21][22][23] Protein kinases that phosphorylate CREB induce binding of CREB to the CRE consensus sequence in chromatin. These kinases include protein kinase A (PKA), [24][25][26] protein kinase C (PKC), 27 p38 and p44 mitogen-activated protein kinases (MAPK), 28,29 and Ca 2 þ -calmodulin kinase (CaMK) IV. 30 Of relevance to bipolar disorder, BDNF levels are decreased in the serum, 31 and BDNF and phosphorylated CREB levels are decreased in the brain of bipolar patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Protein kinases that phosphorylate CREB induce binding of CREB to the CRE consensus sequence in chromatin. These kinases include protein kinase A (PKA), [24][25][26] protein kinase C (PKC), 27 p38 and p44 mitogen-activated protein kinases (MAPK), 28,29 and Ca 2 þ -calmodulin kinase (CaMK) IV. 30 Of relevance to bipolar disorder, BDNF levels are decreased in the serum, 31 and BDNF and phosphorylated CREB levels are decreased in the brain of bipolar patients compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…(24) Phosphorylated CREB binds to cyclic AMP response element (CRE) in the promoter region of genes, which regulates gene expression. (25) This represents an integrative set of mechanisms in which antidepressants acting via either NE or 5-HT can target a common set of genes and their respective protein products.…”
Section: Intracellular Signal Transductionmentioning
confidence: 99%
“…The transcriptional activator CREB was the ®rst member of this class to be described (Hoe er et al, 1988). It has been found that CREB function is tightly regulated by phosphorylation (Yamamoto et al, 1988). Speci®cally, direct phosphorylation by PKA of a serine residue in position 133 converts CREB into a powerful activator (Gonzales and Montminy 1989).…”
Section: Introductionmentioning
confidence: 99%